LNG Cold Energy Recovery for Hydrogen Production Combining Multiple Technologies in Synergy - Carles Troyano Ferré; Rubén Cabello; Laura Muro Marin; Alexandra Plesu; Jordi Bonet-Ruiz; Joan Llorens (Chemical Engineering Transactions)
As a result of the rising global reliance on fossil fuels, freshwater scarcity and environmental problems are getting worse. The process of regasifying liquified natural gas (LNG) releases cold energy, which is often wasted, causes issues for the environment, and increases energy system inefficiencies. This project aims to enhance the sustainability of LNG regasification plants by effectively harnessing this cold energy. The research proposes using this cold energy in four main areas: seawater desalination, hydrogen production, power generation, and carbon dioxide liquefaction. The study explores creating a process that combines Steam Methane Reforming (SMR) with carbon capture and solar-powered water electrolysis, using the organic Rankine cycle for energy recovery and implementing a hybrid desalination process. The majority (82.9 %) of the input liquefied natural gas (LNG) is directed to the natural gas distribution pipeline, the primary function of the regasification facility. For every twelve kilograms of LNG processed, approximately one kilogram of valuable hydrogen is produced. While this hydrogen stream may appear insignificant relative to the complexity of the proposed process from an environmental perspective, it is crucial to acknowledge the low molecular weight of hydrogen. This characteristic implies that a captured and liquefied carbon dioxide (CO2) stream, roughly half the weight of the input LNG, is also collected. This approach enhances environmental sustainability by collecting captured CO2 and energy efficiency, laying the groundwork for future advances in LNG cold energy usage.